Awareness and Acceptability of the Bicol University Vision by the Faculty Members and Non-Teaching Staff in Bu Polangui Campus (BUPC) - Bongat, Clea L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
"This study seeks to determine the extent to which personnel at BU Polangui Campus (BUPC) are aware of and accept the vision of Bicol University. A cross-sectional population survey was conducted using a validated questionnaire. Descriptive and correlational analyses were applied to data from 76 out of 85personnel. Results indicate that the average awareness rating was 92% (Outstanding). Among respondents, 92% accepted the vision, 1.32% found it unacceptable, and 6.58% did not respond. These findings suggest that BUPC personnel are not only fully aware of the vision but also largely accept it."The results indicate that, overall, BUPC staff have a high level of awareness and acceptability of the university’s vision. However, discrepancies in responses suggest that some staff members may struggle to fully engage with the vision, particularly non-teaching staff. The findings suggest that factors such as communication strategies and organizational culture may influence the varying levels of acceptance. The study concludes that clear and consistent communication of the university’s vision, alongside targeted interventions for staff with reservations, is essential for fostering greater alignment and achieving institutional goals. Recommendations include enhancing communication efforts and creating opportunities for all staff to contribute to the realization of the vision.